What is more strongly related to disordered eating in male surfers, body fat or muscularity? - Leonardo de Sousa Fortes; Hugo Augusto Alvares da Silva Lira; Pedro Henrique Berbert de Carvalho; Maria Elisa Caputo Ferreira; Sebastião Sousa Almeida (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS This study aimed to analyze the relationship between disordered eating (DE) and dissatisfaction with body fat and the drive for muscularity in male surfing athletes. METHODS The research included a sample of 175 surfers. The Eating Attitudes Test was used to assess DE. It was used the Body Shape Questionnaire to assess body dissatisfaction based on body fat. It was used the Drive for Muscularity Scale to evaluate the drive for muscularity. RESULTS The multinomial regression model showed a statistically significant association between DE and both body dissatisfaction based on body fat (Wald = 22.97, OR = 3.86) and the drive for muscularity (Wald = 12.38, OR = 1.84). CONCLUSION It was concluded that there is relationship between body dissatisfaction based on body fat and DE. Likewise, there is relationship between drive for muscularity and DE in male surfers.